Pengaruh Literasi Keuangan, Persepsi Risiko dan Pendapatan terhadap Kepuasan Investasi Mahasiswa STIE Surakarta - Luthfi Diah Kurnia Idayanti; Dianing Widya Kusumastuti (Jurnal Ekonomi Manajemen Akuntansi, 2025)
This study focuses on analyzing how financial literacy, risk perception, and income level influence investment decision-making among students. The background of this analysis arises from the low understanding of financial management and the importance of risk considerations in investment among students. A quantitative survey method was employed, involving 93 students selected through purposive sampling. Data were processed using multiple linear regression analysis along with validity, reliability, and classical assumption tests. The findings indicate that financial literacy and risk perception have a significant positive effect on investment decisions, while income does not have a partial effect. Simultaneously, all three variables positively influence investment decisions. These results emphasize the need for students to understand financial literacy and risk awareness to make informed investment decisions. The practical implications of this study support the development of effective financial education for students and serve as a reference for future research on investment behavior and personal financial management.